The Effect of Cash Management On Financial Performance With Accounts Receivable Management As An Intervening - Muhammad Ali Aqsa; Herispon Herispon; Norhayati Binti Md Isa (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2026)
This study examined the effect of cash management on financial performance with accounts receivable management as a mediating variable among board members of KUD X in Rokan Hulu Regency. The cooperative functions as a guarantor for member loans from regional banks, which creates receivable risks requiring careful oversight. A quantitative causal design was employed. The population consisted of 43 board members, and a census sampling method was applied. Data were collected through questionnaires using a five-point Likert scale. Analysis utilized JASP and SPSS software. The results showed that cash management positively and significantly affected accounts receivable management. Accounts receivable management positively and significantly affected financial performance. Cash management also had a positive and significant direct effect on financial performance. Bootstrapping confirmed that accounts receivable management significantly mediated this relationship (indirect effect. The findings confirm that effective cash management improves receivable handling, which in turn enhances financial performance. The study contributes to agency theory and signaling theory in the context of cooperatives acting as loan guarantors.